Quantitative image analysis as a robust tool to assess effluent quality from an aerobic granular sludge system treating industrial wastewater - Costa, Joana Sofia Gomes (2022)
Supplementary data to this article can be found online at https://doi.org/10.1016/j.chemosphere.2021.132773.